Big data challenges in overcoming China’s water and air pollution: relevant data and indicators - Zhang, Bo; Hughes, Robert M.; Davis, Wayne S.; Cao, Cong (2021)
Big data are potentially useful for environmental management planning and actions that can be directed toward pollu-tion control. China is using big data approaches to help reduce its current levels of pollution. However, also needed are better environmental indicators, measurement technologies, data management and reporting, and adaptive manage-ment and enforcement. Based on continental-extent monitoring and assessment programs in Europe and the USA, we recommend three major programmatic changes for China. (1) Establish long-term systemic environmental and human health objectives and indicators. (2) Adopt national standard methods for survey designs, sampling and analytical pro-tocols, statistical analyses, and collaborative sampling programs. (3) Provide a transparent process for reporting and correcting data errors.